1991
DOI: 10.1103/physrevlett.67.2387
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the layer-by-layer growth of initial oxide layers on Si(100) surface during thermal oxidation

Abstract: We present the results of an x-ray photoelectron spectroscopy investigation in the real-time regime of the kinetics of high-temperature oxidation of the Si(100) surface. The dependence of the net concentration of silicon atoms in all oxidation states (i.e., Si ,+ , Si 2+ , Si 3+ , Si 4+ ) on oxygen exposure is found to exhibit a "step"-like behavior, each "step" corresponding to one oxide layer. The results obtained suggest a mechanism of layer-by-layer growth of initial oxide layers, with oxide-phase formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 20 publications
1
12
0
3
Order By: Relevance
“…Since the calculated resolution for this low loss region is ϳ1 nm, this low oxidation state of Si 1.32ϩ implies that the rate of oxidation at the Si/SiO x interface is limited by the diffusion of oxidizing species through the Zr-O layer. 63,64 A schematic of the nanostructure and nanochemistry that has evolved in the annealed Zr-O/IL/Si stack is illustrated in Fig. 12.…”
Section: High-resolution Transmission Electron Microscopy and Parallementioning
confidence: 99%
“…Since the calculated resolution for this low loss region is ϳ1 nm, this low oxidation state of Si 1.32ϩ implies that the rate of oxidation at the Si/SiO x interface is limited by the diffusion of oxidizing species through the Zr-O layer. 63,64 A schematic of the nanostructure and nanochemistry that has evolved in the annealed Zr-O/IL/Si stack is illustrated in Fig. 12.…”
Section: High-resolution Transmission Electron Microscopy and Parallementioning
confidence: 99%
“…8 The passive oxidation modes have been recently identified by real-time measurement with photoemission spectroscopic methods. [5][6][7] The passive oxidation can be subdivided into Langmuir-type adsorption and the two-dimensional island growth. 5,6 At an oxygen pressure of 2.7ϫ 10 −5 Pa and a temperature between 853 and 913 K, the uptake curve of O͑2p͒ intensity exhibits an exponential curve for Langmuir-type adsorption, while it follows a sigmoid curve for two-dimensional island growth.…”
Section: Introductionmentioning
confidence: 99%
“…The initial growth modes have recently been identified by real-time measurement with Auger electron spectroscopy ͑AES͒, 5 ultraviolet photoemission spectroscopy ͑UPS͒, 6 and x-ray photoemission spectroscopy. 7 Oxidation modes on Si͑001͒ can be classified into two regimes. Over a wide range of pressure-temperature conditions, there is a critical curve which separates the oxidation modes for which etching is the dominant process ͑active oxidation regime͒ from those which produce SiO 2 growth ͑pas-sive oxidation regime͒.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the atomic level, the oxidation mechanism is not yet completely understood. Recently, the layer-by-layer process model, where oxidation is modeled as a layer-by-layer process at the SiO 2 /Si interface, was proposed from the measurements of high-resolution transmission electron microscopy (TEM), scanning reflection electron microscopy (SREM), reflection high-energy electron diffraction, and X-ray photoelectron spectroscopy (XPS) [6][7][8][9][10][11][12][13][14][15][16]. In this study, we directly observed the morphology change of the SiO 2 /Si(111) interfaces of oxide films grown at different temperatures, 1050 and 900°C, with various thickness from 4 to 14 nm under near normal conditions where metal-oxidesemiconductor devices are fabricated.…”
Section: Introductionmentioning
confidence: 99%